An Egypt Amarna letter (EA 162) and word order variation of the verbal sentences - van der Westhuizen, J. P. (Journal for semitics, 2012)
The correspondence between the vassals of Syria-Palestine and their sovereign, the pharaoh of Egypt, was instigated by the external and internal turmoil in Syria-Palestine during the Late Bronze Age. The letters were written by the scribes of the vassals and the scribes of the pharaoh, in the WPA (Western Peripheral Akkadian) dialect, with some West Semitic (WS) trends. One such trend is the word order, and variations from it, in the verbal sentences. This variation in word order was to effect some special emphasis or some nuance of the appropriate element in the specific sentence. The variation in word order was brought about by certain (emphasizing) words such as anuma, šanita, inuma and amurmi and/or constructions such as subject fronting or object fronting, parallel sentence arrangement and chiastic sentence arrangement. However, even this word order and variations thereof show no consistency. An investigation of the word order and the variations functioning in the verbal sentences of the Amarna-Akkadian letters, such as EA 1621 from the pharaoh, shows that these letters - even those with similar content to the other letters from the pharaoh - must have been written by different scribes of the pharaoh. This leads to the conclusion that each scribe had his own version of an "interlanguage" that he used in his correspondence.